Early alteration of the locus coeruleus in phenotypic variants of Alzheimer’s disease - Olivieri, Pauline (Ann Clin Transl Neurol, 2019)
Neuropathological studies showed early locus coeruleus (LC) neuronal loss associated with tauopathy in Alzheimer’s Disease (AD). We used the LC signal intensity (LC‐I) on 3T MRI to assess the LC integrity in AD (n = 37) and controls (n = 17). The LC‐I was decreased in AD regardless of typical (amnesic) and atypical presentation (logopenic aphasia/visuo‐spatial deficit), from the prodromal stage, and independently of the amyloid load measured by PiB‐PET. The LC‐I was correlated with memory performance of typical AD. This supports the pathophysiological model in which the LC plays a critical role in AD and may thus be a potential therapeutic target.